2000
DOI: 10.1021/jp002566f
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Free Infrared Multiphoton Dissociation of Silane

Abstract: We have measured an upper limit of 17 J/cm2 for the threshold fluence for collision-free CO2 laser IRMPD of silane by detecting the SiH2 product in its electronic and vibrational ground state. The threshold drops to ∼4 J/cm2 when silane molecules are irradiated by all lines from a pulsed NH3 laser. This value further drops to less than 2 J/cm2 when the molecules are pre-excited to the first Si−H stretch overtone. Using the NH3 laser on the 868 cm-1 line, the dissociation yield of pre-excited SiH4 reaches satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The apparatus we employ for these experiments, depicted schematically in Figure , has been described in detail elsewhere. , Briefly, we generate 3−4 mJ of infrared radiation at 4450.5 cm -1 for excitation of the first Si−H stretch overtone by difference frequency mixing the output of a Nd:YAG pumped dye laser with the fundamental of the same pump laser in a LiNbO 3 crystal. As a dissociating laser we use either a home-built NH 3 laser pumped by a pulsed CO 2 laser or the CO 2 laser directly.…”
Section: Methodsmentioning
confidence: 99%
“…The apparatus we employ for these experiments, depicted schematically in Figure , has been described in detail elsewhere. , Briefly, we generate 3−4 mJ of infrared radiation at 4450.5 cm -1 for excitation of the first Si−H stretch overtone by difference frequency mixing the output of a Nd:YAG pumped dye laser with the fundamental of the same pump laser in a LiNbO 3 crystal. As a dissociating laser we use either a home-built NH 3 laser pumped by a pulsed CO 2 laser or the CO 2 laser directly.…”
Section: Methodsmentioning
confidence: 99%
“…Implementation of such a scheme for SiH 4 is complicated by the lack of rotational assignments of the first Si−H stretch overtone band of silane. Moreover, our previous investigations revealed that efficient IRMPD of vibrationally pre-excited SiH 4 using a particular line of a NH 3 laser occurs only if the first laser pre-excites the molecules to a particular rotational state . We attribute this selectivity to the requirement that the first few steps of IRMPD be nearly resonant with the frequency of the NH 3 laser when the dissociating fluence is low.…”
Section: Introductionmentioning
confidence: 90%
“…In contrast, when the molecules are pre-excited to the first Si−H stretch vibrational overtone before IRMPD, the dissociation is more efficient and exhibits lower threshold fluence. We estimate that vibrational pre-excitation increases the dissociation cross-section by a factor of 230 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The IRLAPS detection technique has been used over the past decade for measuring spectra of highly vibrationally excited molecules such as CF 3 H, 17,18 SiH 4 , 19,20 and methanol, 12,[21][22][23] and the experimental details have been previously described. 21,24 -27 We briefly summarize this technique as applied to the present experiments.…”
Section: Experimental Approachmentioning
confidence: 99%